The effects of exercise-induced muscle damage on varying intensities of endurance running performance: A systematic review and meta-analysis - Burt, D.; Doma, K.; Connor, J. (Science & Sports, 2023)
Objectives This systematic review and meta-analysis investigated the effects of exercise-induced muscle damage (EIMD) on sub-maximal and maximal effort running performance.